2020
DOI: 10.3390/ijms21249518
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Interactions between Self-Assembled β-Sheet Peptide Nanofibers and Model Cell Membranes

Abstract: Self-assembled peptide nanofibers (NFs) obtained from β-sheet peptides conjugated with drugs, including antigenic peptides, have recently attracted significant attention. However, extensive studies on the interactions of β-sheet peptide NFs with model cell membranes have not been reported. In this study, we investigated the interactions between three types of NFs, composed of PEG-peptide conjugates with different ethylene glycol (EG) lengths (6-, 12- and 24-mer), and dipalmitoylphosphatidylcholine (DPPC) Langm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The authors suggested in another study that long hydrophilic chains incorporated into the peptide nanofiber structure could limit the hydrophobic interaction with the APCs’ cell membrane. 72 These studies investigated the effects of peptide nanofiber components on cellular interactions, aiming to bridge the gaps between materials science and immune modulation.…”
Section: Peptide Nanofibersmentioning
confidence: 99%
“…The authors suggested in another study that long hydrophilic chains incorporated into the peptide nanofiber structure could limit the hydrophobic interaction with the APCs’ cell membrane. 72 These studies investigated the effects of peptide nanofiber components on cellular interactions, aiming to bridge the gaps between materials science and immune modulation.…”
Section: Peptide Nanofibersmentioning
confidence: 99%